2016
DOI: 10.23910/ijbsm/2016.7.5.1526
|View full text |Cite
|
Sign up to set email alerts
|

Apis cerana F. as an Important Natural Pollinator of Radish (Raphanus sativus L.) under Mid-hill Conditions of Himachal Pradesh

Abstract: The present studies were undertaken to find out the pollination efficiency of Apis mellifera L. and other natural pollinators in radish (cv. Pusa Himani) and their impact on yield and quality of seeds under mid hill conditions of Himachal Pradesh. A. cerana was dominant amongst all insect visitors being 5.85 and 6.6 bees m -2 5 minutes -1 in 2011 and 2012, respectively. A. mellifera (introduced bee species) population was quite low (0.3) during 2011 which clearly indicated that the bees did not get conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…rl 2210 long (g2) had the highest negative interaction with environment and also higher root length than mean indicated its greater resistance to environmental changes. Findings of the present study were in consonance with those of Sharma et al (2002).…”
Section: Resultssupporting
confidence: 91%
“…rl 2210 long (g2) had the highest negative interaction with environment and also higher root length than mean indicated its greater resistance to environmental changes. Findings of the present study were in consonance with those of Sharma et al (2002).…”
Section: Resultssupporting
confidence: 91%
“…More or less similar results were obtained by Singh 2). It was observed that 140 loose pollen grains were found adhering to the body of E. balteatus foraging on radish (Sharma et al, 2016). The pollination index showed that Eristalini (12.52) scored higher than Syrphini (8.14) during 2018; and in 2019, these values were 9.63 and 7.14.…”
Section: Resultsmentioning
confidence: 99%